Distribution of polycyclic aromatic hydrocarbons in agricultural soils and vegetations in subtropical zone - HAO Rong; WAN Hong-fu; DU Wei-bing; PENG Shao-lin (浙江大学学报. 农业与生命科学版)
Distribution of EPA Priority Polycyclic Aromatic Hydrocarbons (PAH) in Agricultural Soils and vegetation from subtropical zone of China was studied. Soil samples and vegetation samples from Shantou were collected during March and November 2002 and PAH were identified using gas chromatography linked to mass spectrometry (GC-MS). PAH in soils was dominated by three-ring and four-ring PAH and the dominant individual PAH was naphthalene, phenanthrene, fluoranthene and beozo [b] fluornthene. However, PAH in vegetations dominated by three-ring PAH and the dominant individual PAH was naphthalene, phenanthrene. PAH would efficiently mobilization and transportation in the 0-100cm soil layer, thereinto the rate of input of PAH to the upper soils was higher than the rate of mobilization and transport. The factor influencing on PAH distribution in soils and vegetations were not only PAH own physical and chemic property but also physical and chemic character of soils, types of vegetations and environment conditions.